Kinematic modifications induced by the introduction of the lateral inspiration in the butterfly stroke - Barbosa, T.; Sousa, F.; Vilas-Boas, J. P. (1999)
Summary The purpose of this study was to examine changes in the body's motion through the water when side breathing is introduced in butterfly. Very little research has been done to see how breathing to the side may alter stroke mechanics, potentially making butterfly either more or less efficient. Intuition suggests that side breathing may be more efficient, since the head does not have to be lifted as high to breathe. Thus, the swimmer may be better able to maintain his/her bodyline in the water. However, there are other issues (i.e. excessive body rotation) that could be introduced based on an athlete's shoulder flexibility. These researchers examined 7 elite level swimmers, proficient at both front and side breathing, as they swan both styles of butterfly. Side breathing and front breathing trials were swum at the same paces to allow for direct comparison. Swims were filmed with two cameras and images were digitized to measure positions and velocities of the hands, head, shoulders, hips, knees and ankles. Specifically, the investigators looked to see if body alignment changed significantly when an athlete breathed to the side as opposed to breathing to the front. From the results, suggestions could then be made as to which technique might be better. Findings There were no significant differences were found in the body motion between front breathing and side breathing for any body part other than the head. The maximal height that the head reaches above the water was significantly higher for front breathing when compared to side breathing. There is some rotation around the long axis of the body when the swimmer breathes to the side. While not statistically significant, there are trends for the hips to be lower in the water and for the shoulders to be higher in the water during front breathing. Timing issues and balance issues were not investigated in this study. Implications (Comments made by Scott Riewald, USA Swimming's Biomechanics Director) The findings of this study show that some changes may be introduced into a swimmer's body line when they breathe to the side as opposed to the front. Side breathing may make the butterfly swimmer more streamlined. If the head and shoulders do not come out of the water as high, typically the hips do not drop as low in the water and the swimmer experiences less drag (a good thing). Body rotation about the long axis of the body in butterfly may cause the swimmer to have an asymmetrical pulling pattern. Watch your athlete and ask for feedback to determine if the pulling mechanics are being "thrown off" by the side breathing. If your athlete breathes to the side, work to increase shoulder flexibility. This flexibility may be needed for the hands to clear the water as the body takes a lower trajectory/ bodyline through the water. While this study did not address balance and/ or timing of the stroke, keep in mind that these variables may be affected. Work with your athletes to optimize these variables as well. (In: Biomechanics and Medicine in Swimming VIII. Keskinen, K., Komi, P and Hollander, P. (Eds). Jyväskyla, Finnland.)